2021
DOI: 10.1053/j.gastro.2020.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleus and In Situ RNA–Sequencing Reveal Cell Topographies in the Human Pancreas

Abstract: BACKGROUND & AIMS: Molecular evidence of cellular heterogeneity in the human exocrine pancreas has not been yet established because of the local concentration and cascade of hydrolytic enzymes that can rapidly degrade cells and RNA upon pancreatic resection. We sought to better understand the heterogeneity and cellular composition of the pancreas in neonates and adults in healthy and diseased conditions using single-cell-sequencing approaches. METHODS: We innovated single-nucleus RNA-sequencing protocols and p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
143
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(177 citation statements)
references
References 57 publications
(59 reference statements)
19
143
1
Order By: Relevance
“…The two essential components for PDAC development are: (1) acquisition of an oncogenic mutation by acinar or ductal cells, with KRAS oncogene counting for 90% of cases; (2) inflammation within microenvironment which drives early lesion development. Multiple scRNA-Seq studies in PDAC mouse models and human tumor samples shed light on tumor cell identity and heterogeneity, as well as tumor microenvironment (TME), including role of cancer associated fibroblasts (CAFs) and immune landscape, and cross-talk between tumor and TME ( Ting et al, 2014 ; Bernard et al, 2019 ; Elyada et al, 2019 ; Hosein et al, 2019 ; Ligorio et al, 2019 ; Peng et al, 2019 ; Dominguez et al, 2020 ; Hwang et al, 2020 ; Lee et al, 2020 ; Schlesinger et al, 2020 ; Steele et al, 2020 ; Zhou et al, 2021 ). These studies showed that intra-tumor heterogeneity identified by scRNA-Seq is reliable as a prognostic marker and can be used for personalized treatment choice.…”
Section: Non-diabetic Diseases Of Pancreasmentioning
confidence: 99%
See 4 more Smart Citations
“…The two essential components for PDAC development are: (1) acquisition of an oncogenic mutation by acinar or ductal cells, with KRAS oncogene counting for 90% of cases; (2) inflammation within microenvironment which drives early lesion development. Multiple scRNA-Seq studies in PDAC mouse models and human tumor samples shed light on tumor cell identity and heterogeneity, as well as tumor microenvironment (TME), including role of cancer associated fibroblasts (CAFs) and immune landscape, and cross-talk between tumor and TME ( Ting et al, 2014 ; Bernard et al, 2019 ; Elyada et al, 2019 ; Hosein et al, 2019 ; Ligorio et al, 2019 ; Peng et al, 2019 ; Dominguez et al, 2020 ; Hwang et al, 2020 ; Lee et al, 2020 ; Schlesinger et al, 2020 ; Steele et al, 2020 ; Zhou et al, 2021 ). These studies showed that intra-tumor heterogeneity identified by scRNA-Seq is reliable as a prognostic marker and can be used for personalized treatment choice.…”
Section: Non-diabetic Diseases Of Pancreasmentioning
confidence: 99%
“…PDAC can develop when control over a physiological regeneration of exocrine pancreas fails ( Storz, 2017 ). The regeneration is driven by a reversible process of acinar cells dedifferentiation into duct-like exocrine progenitors (acinar-to-ductal metaplasia, ADM), and the transitional, plastic populations were observed in adult human pancreata and PDAC samples by scRNA-Seq ( Qadir et al, 2020 ; Zhou et al, 2021 ) and single-nucleus RNA-Seq (sNuc-Seq) ( Tosti et al, 2021 ). The irreversible dedifferentiation and unrestrained proliferation of these progenitors leads to pancreatic intraepithelial neoplastic lesions (PanIN) and eventually PDAC ( Storz, 2017 ).…”
Section: Non-diabetic Diseases Of Pancreasmentioning
confidence: 99%
See 3 more Smart Citations